Integrated Management of Late Blight Potato (Phytophthora infestans, (Mont) de Bary) Disease through Potato Varieties and Fungicides in Lay-Armachiho District, Ethiopia. (23rd August 2022) - Teshome, Zewdu; Sintayehu, Asefa; Zeleke, Asefa
Abstract : Potato ( Solanum tuberosum L.) is an important source of livelihood for smallholder farmers of north-western Ethiopia. However, its productivity is markedly low due to late blight disease caused by Phytophthora infestans . The objective of this study was to evaluate the integrated use of potato varieties and fungicides for the management of late blight disease. Field experiment was conducted in Lay-Armachiho district during the main potato cropping season of 2018. The experiment consisted of twelve treatments as factorial combinations of two synthetic fungicides (Ridomil and Mancozeb) and untreated check with four potato varieties (three improved varieties, namely, Jalene, Gudene, Belete, and Local variety) was laid out in RCBD design with three replications. Disease incidence, severity, AUDPC, yield, and yield components were analyzed using SAS software (version 9.1) at P < 0.05 to separate treatment means. Fungicide sprayed treatments significantly reduced late blight epidemics and increased potato tuber yield on the Belete variety. The lowest disease severity (38.50%) and AUDPC values (761.02% unit-days) were recorded on Belete variety when sprayed with Ridomil fungicide. Late blight disease severity, incidence, AUDPC, and disease progress rate were reduced more in Belete variety than in the other three varieties. The highest disease severity (91.40%) and lowest yield (10.63 ton·ha −1 ) were recorded from the local control plot with a clear significance difference as compared to other treated plots. This study revealed that the application of Ridomil fungicide with the combination of Belete variety was effective in controlling late blight potato disease with the highest cost-benefit advantage.